DEVELOPMENT OF THE REMOTE-PILOTED VEHICLE ALGORITHMIC SUPPORT AND ON-BOARD NAVIGATION COMPLEX STRUCTURE - Mykyjchuk, Mykola; Markiv, Volodymyr (Informatyka, automatyka, pomiary w gospodarce i ochronie środowiska, 2018)
The article dwells upon the peculiarities of remote piloted vehicles of on-board navigation complex. It is highlighted that total number of the remote-piloted vehicles have increased and as a result the question of their integration into common space with manned aircraft becomes urgent. It is possible only when specified quality of the remote piloted vehicle movement parameters have been determined, including accuracy and interference immunity. It has been highlighted that remote-piloted vehicle equipment is subject to stringent requirements for minimization of cost, mass and size characteristics and power consumption, which are often mutually contradictory, and their implementation in general leads to deterioration of accuracy. The problem of ensuring accuracy and noise immunity when using the general-purpose element base becomes urgent.